Wampum and the origins of American money - Shell, Marc.; American Numismatic Society (1907- ) (Urbana, IL : University of Illinois Press, 2013)
"Wampum has become a synonym for money, and it is widely assumed that it served the same purposes as money among the Native Algonquians even after coming into contact with European colonists' money. But to equate wampum with money only matches one slippery term with another, as money itself was quite ill-defined in North America for decades during its colonization. Fledgling colonial currencies assimilated much more from Native American trading practices than they imposed on the locals, so much so that colonists regularly expressed fears of "becoming Indians" in their widespread use of paper money, a novel economic innovation adapted from wampum. In this stimulating and intriguing book, Marc Shell illuminates the context in which wampum was used by describing how money circulated in the colonial period and the early history of the United States. Wampum itself, generally tubular beads made from clam or conch shells, was hardly a primitive version of a coin or dollar bill, as it represented to both Native Americans and colonial Europeans a unique medium through which language, art, culture, and even conflict were negotiated. This wide-ranging exploration of economics, literature, and racial and ethnic imagery throughout American history is extensively illustrated with more than a hundred images of documents, artworks, and artifacts, including numerous depictions of Native Americans on paper money."--Jacket.
Introduction : why wampum? -- Money and language -- Foreign legal tender -- Translation and conversion -- Coins on paper -- What is wampum? -- Indian giving and Willie Wampum -- Money writing -- Civilization -- Wall Street and democracy -- What happened to wampum.
Includes bibliographical references (pages 101-129) and index.
Keywords: Wampum; Indians of North America -- Money; Money -- United States -- History -- Colonial period, ca. 1600-1775.; Indians of North America -- Money; Money -- Colonial period; Wampum; United States; Indianer; Wampum; Zahlungsmittel; Nordamerika; Indianer; Wampum; Zahlungsmittel; Banknote; Indianer; Nordamerika; USA; Wampum; Monnaie -- Histoire; Pengar -- historia; Nordamerikas indianer; Wampum; Indians of North America -- Money; Money -- United States -- History -- Colonial period, ca. 1600-1775.; 1600-1775; 1600-talet; 1700-talet; History